An experimental study of spatial sound usefulness in searching and navigating through AR environments. Issue 3 (November 2015) - Rumiński, Dariusz
Abstract This paper presents an experimental study of spatial sound usefulness in searching and navigating through augmented reality environments. Participants were asked to find three objects hidden within no-sound and spatial sound AR environments. The experiment showed that the participants of the spatialized sound group performed faster and more efficiently than working in no-sound configuration. What is more, 3D sound was a valuable cue for navigation in AR environment. The collected data suggest that the use of spatial sound in AR environments can be a significant factor in searching and navigating for hidden objects within indoor AR scenes. To conduct the experiment, the CARE approach was applied, while its CARL language was extended with new elements responsible for controlling audio in 3D space.